Soybean Roots Grown under Heat Stress Show Global Changes in Their Transcriptional and Proteomic Profiles - Valdés-López, Oswaldo; Batek, Josef; Gomez-Hernandez, Nicolas; Nguyen, Cuong T.; Isidra-Arellano, Mariel C.; Zhang, Ning; Joshi, Trupti; Xu, Dong; Hixson, Kim K.; Weitz, Karl K.; Aldrich, Joshua T.; Paša-Tolić, Ljiljana; et al. (Frontiers in Plant Science, 2016)
Heat stress is likely to be a key factor in the negative impact of climate change on crop production. Heat stress significantly influences the functions of roots, which provide support, water and nutrients to other plant organs. Likewise, roots play an important role in the establishment of symbiotic associations with different microorganisms. Despite the physiological relevance of roots, few studies have examined their response to heat stress. In this study, we performed genome-wide transcriptomic and proteomic analyses on isolated root hairs, which are a single, epidermal cell type, and compared their response to stripped roots. On average, we identified 1,849 and 3,091 genes differentially regulated in root hairs and stripped roots, respectively, in response to heat stress. Our gene regulatory module analysis identified ten key modules that might control the majority of the transcriptional response to heat stress. We also conducted proteomic analysis on membrane fractions isolated from root hairs and compared these responses to stripped roots. These experiments identified a variety of proteins whose expression changed within 3 hours of application of heat stress. Most of these proteins were predicted to play a significant role in thermo-tolerance, as well as in chromatin remodeling and post-transcriptional regulation. The data presented represent an in-depth analysis of the heat stress response of a single cell type in soybean.